Efforts to Improve Early Childhood Numeracy Skills through Playing Number Envelopes at RA Sirojul Muttaqiin - Ovianti, Wahyu; Romadhoni, Wahyu; Mila, Via El; Khasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2024)
This study used Classroom Action Research (CAR) which was implemented in two cycles, with each cycle having planning, implementation, observation, and reflection. The data source was students of Group B RA Sirojul Muttaqiin, Lemawungkuk District, Cirebon City through more interesting learning activities by playing number envelopes with the theme as a learning resource proven to be able to improve early arithmetic skills of early childhood, which can be seen from the data sheet of observation results during the arithmetic learning activities. In cycle I, the results obtained were 50% increase in early arithmetic learning skills not by playing, while in cycle II, the increase in early arithmetic learning skills by playing was 82.05% with these results indicating that this study was successful because it exceeded the target of the research indicator by 80%. The results of this study indicate that playing number envelopes as a learning resource can be said to be successful in improving early arithmetic skills of early childhood. Based on this study, it is recommended that all teachers can provide interesting and enjoyable geometric shape learning for children. Teachers should also be able to create a comfortable and enjoyable learning environment for children. Based on these conditions, the formulation of the problem presented in this writing is: playing number envelopes that can be used to develop early numeracy skills in Group B RA Sirojul Muttaqiin, Lemahwungkuk District, Cirebon City and how to improve early numeracy skills by playing number envelopes in Group B RA Sirojul Muttaqiin, Lemahwungku District, Cirebon City. In cycle I, the results obtained were 50% increase in early numeracy learning skills without playing, while in cycle II, the increase in early numeracy learning skills by playing was 82.05% with these results indicating that this study was successful because it exceeded the target of the research indicator by 80%. The results of this study indicate that playing number envelopes as a learning resource can be said to be successful in improving early numeracy skills in early childhood. Based on this study, it is recommended that all teachers can provide interesting and enjoyable geometric shape learning for children. Teachers should also be able to create a comfortable and enjoyable learning environment for children